Malignancy can present as acute liver failure – a case report of B-cell lymphoma with acute liver failure as its first presentation - Catarina Melita; Joaquim Tinoco; Rita Theias Manso; Liliana Antunes; Mónica Palma Anselmo; Paulo Telles de Freitas (European Journal of Case Reports in Internal Medicine)
Malignant infiltration of the liver is a rare cause of acute liver failure and is associated with an exceedingly high mortality rate. We describe the case of an elderly woman presenting with fulminant hepatitis and simultaneous type B lactic acidosis, with near-normal imaging findings, who was later demonstrated to have non-Hodgkin lymphoma. The presence of acute liver failure, hepatomegaly, markedly elevated lactate dehydrogenase and/or lactic acidosis should raise suspicion for lymphoma infiltration of the liver and prompt liver biopsy early in the course of disease. We hope to raise awareness for this uncommon and elusive presentation of lymphoma, in the hope that it will help achieve earlier diagnoses and improvements in patient survival.